2015
DOI: 10.1007/s11469-015-9592-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Video Game Addiction: A Study Based on a National Representative Sample of Gamers

Abstract: Video gaming has become a popular leisure activity in many parts of the world, and an increasing number of empirical studies examine the small minority that appears to develop problems as a result of excessive gaming. This study investigated prevalence rates and predictors of video game addiction in a sample of gamers, randomly selected from the National Population Registry of Norway (N = 3389). Results showed there were 1.4 % addicted gamers, 7.3 % problem gamers, 3.9 % engaged gamers, and 87.4 % normal gamer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
194
7
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 303 publications
(245 citation statements)
references
References 36 publications
26
194
7
18
Order By: Relevance
“…These findings may stimulate cross-cultural research on IGD, since a very few studies have used random and representative samples to estimate the prevalence rates of IGD using the latest diagnostic framework provided by the APA. The prevalence figures obtained in this study are very similar to those reported in the previous studies using representative samples that found IGD prevalence rates to be around 1.4% in the Norwegian general population (Wittek et al., 2015), 3.6% in early adolescents from five European countries (i.e., Estonia, Germany, Italy, Romania, and Spain) (Strittmatter et al., 2015), 1.6% in European adolescents from seven European countries (i.e., Germany, Greece, Iceland, Netherlands, Poland, Romania, and Spain) (Müller et al., 2015), 3% in Dutch adolescents (Van Rooij, Schoenmakers, Vermulst, Van Den Eijnden, & Van De Mheen, 2011), and 4.3–6.7% in Hungarian adolescents (Király et al., 2014). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings may stimulate cross-cultural research on IGD, since a very few studies have used random and representative samples to estimate the prevalence rates of IGD using the latest diagnostic framework provided by the APA. The prevalence figures obtained in this study are very similar to those reported in the previous studies using representative samples that found IGD prevalence rates to be around 1.4% in the Norwegian general population (Wittek et al., 2015), 3.6% in early adolescents from five European countries (i.e., Estonia, Germany, Italy, Romania, and Spain) (Strittmatter et al., 2015), 1.6% in European adolescents from seven European countries (i.e., Germany, Greece, Iceland, Netherlands, Poland, Romania, and Spain) (Müller et al., 2015), 3% in Dutch adolescents (Van Rooij, Schoenmakers, Vermulst, Van Den Eijnden, & Van De Mheen, 2011), and 4.3–6.7% in Hungarian adolescents (Király et al., 2014). …”
Section: Discussionsupporting
confidence: 91%
“…Although reliable prevalence rates of IGD across many populations are lacking due to the limitations in the assessment (Petry, Rehbein, Ko, & O’Brien, 2015), findings from studies including representative samples have reported IGD rates of approximately 8.5% in American youth aged 8–18 years (Gentile, 2009), 1.2% in German adolescents aged 13–18 years (Rehbein, Kliem, Baier, Mößle, & Petry, 2015), 5.5% in Dutch adolescents aged 13–20 and 5.4% in Dutch adults (Lemmens, Valkenburg, & Gentile, 2015), 4.3% in Hungarian adolescents aged 15–16 years (Király et al., 2014), 1.4% in Norwegian gamers (Wittek et al., 2015), and 1.6% in youth from seven European countries aged 14–17 years (Müller et al., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…2) Study populations with comparable demographics and recruitment (mixed/single gender, urban/rural, similar ages, cultures) and studying the disorder across age groups/cultures (60,61). 3) Clear data regarding comorbid diagnoses and personality ratings to ascertain to what extent IGD occurs independently of ADHD, depression, anxiety, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Although the positive effects of health gaming have been demonstrated by a large body of research, [1][2][3][4] numerous studies have systematically reported potentially harmful effects games can have on human health due to its potentially addictive properties [5][6][7] and overall detrimental effects [8][9][10][11] in several life domains for a minority of gamers. Such harmful effects related to addiction to gaming can include decreased levels of exercise and sports, 12 impaired decision-making, 13 poorer psychosomatic health, 14 greater incidence of psychiatric symptoms, 15 lower expected college engagement and grades in adolescent students, 5 compromised prefrontal cognitive control over emotional interference, 16 in addition to other psychiatric disorders and abnormal behaviors. 11,17,18 In light of this, the latest (fifth) edition of the American Psychiatric Association's (APA) Diagnostic and Statistical Manual of Mental Disorders 19 included Internet…”
Section: Introductionmentioning
confidence: 99%